A study on factors that is influence the performance of commercial bank in China using financial ratio/ Ismail Mohammed Sufian - Mohammed Sufian, Ismail (2018)
The purpose of this study is to determine the factors that influence the performance of commercial banks in China by using financial ratio. Performance of commercial bank is very important for the stakeholders and investors, in order to know whether the banks are doing good in reducing risk and getting higher return. To evaluate the performance of commercial banks in China is done by using the financial ratio such as Return on Asset (ROA), Return on Equity (ROE) and Net Interest Margin (MM) Nevertheless, for this study it will focus more on Return on Asset (ROA) as a dependent variable. Meanwhile, the independent variables will be used as a factors that influences the performance of banking sectors are asset quality, bank size, Total Debt to Total Asset, customer deposit, capital ratio and bank liquidity. This study will use a sample of 5 commercial banks in China and the period for 10 years from 2008 to 2017. The data had been collected through data stream and Thompson Eikon Routers. Furthermore, the study uses a panel data analysis, descriptive analysis, correlation analysis and multiple regression analysis by used the pooled Ordinary Least Squares (OLS) method. The study also includes the assumption test too. The study identified that the independent variables have a relationship with the dependent variable.